A rapid fungal DNA extraction method suitable for PCR screening fungal mutants, infected plant tissue and spore trap samples. (January 2022) - Pilo, Paola; Tiley, Anna M.M.; Lawless, Colleen; Karki, Sujit J.; Burke, James; Feechan, Angela
Abstract: Current DNA extraction methods from filamentous fungi take from an hour to a full day. These methods require buffers and tools for grinding fungal tissues. Although commercial extraction kits can reduce the amount of time spent preparing and extracting genomic DNA from fungal samples, these can be expensive. Here we describe a quick and inexpensive sonication technique to extract genomic DNA from filamentous fungi without buffer which can be used to perform PCR in under an hour. DNA was extracted from Zymoseptoria tritici, Fusarium graminearum and Botrytis cinerea in vitro cultures, Z. tritici asexual fruiting bodies and directly from spore trap tapes. Highlights: A sonication method allows the quick and inexpensive extraction of fungal pathogen DNA. This sonication method gave sufficient DNA yield and quality from fungal tissue and spore trap tapes for PCR analysis. The extracted fungal DNA was used for multiplex PCR to detect virulence genes from Zymoseptoria tritici.